A comparative study of caffeinated beverages; tea and energy drink consumption on attention span of healthy male and female subjects - Zafar, Kiran; Naeem, Arfa; Mirza, Faizan (International Journal of Endorsing Health Science Research, 2016)
Tea is the most widely consumed beverage after water around the globe with consumer-base of both young and old, while energy drinks are popular primarily among young adults. Among the different varieties available black tea is the most commonly used and contains L-Theanine, theobromine, theophylline and the highest amount of caffeine. Energy drinks on the other hand contain taurine, herbs, B vitamins and stimulant drugs chiefly caffeine. The purpose of the study conducted was to evaluate the effect of regular tea and energy drinks on attention. A survey was conducted and subjects were given a task that was designed to test the above mentioned parameter and time taken to solve each part of the task was accurately noted. Results of the energy drink group and the tea group were compared to the control group. Gender based differences were also analyzed. Our results lead us to conclude that the most widely taken beverages enhance attention in both genders, with women outperforming men.